1990
DOI: 10.1111/j.1365-246x.1990.tb05574.x
|View full text |Cite
|
Sign up to set email alerts
|

A theory of spectral analysis based on the characteristic property of a linear dynamic system

Abstract: S U M M A R YWe present a detailed description of a new method of spectral analysis named 'Sompi'. The basic idea of this method originates in the physical concept of the characteristic property of the linear dynamic system that is described by a linear differential equation. The time series modelling in the Sompi method consists essentially of estimating the governing differential equation of the hypothetical linear dynamic system that has yielded the given time series data. Due to the equivalence of a linear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
64
0
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(69 citation statements)
references
References 19 publications
1
64
0
4
Order By: Relevance
“…In addition, analysis of the complex frequencies of selected LP events is consistent with a steam-filled crack. We applied the Sompi method [Kumazawa et al, 1990] to the source time function of our model crack and found growth rates for our dominant frequency that are consistent with low Q values of 10 -20. Such high attenuation can be attributed to bubbly magma, bubbly water, or steam [e.g., Kumagai and Chouet, 2000;Kumagai et al, 2005].…”
Section: Source Processmentioning
confidence: 99%
“…In addition, analysis of the complex frequencies of selected LP events is consistent with a steam-filled crack. We applied the Sompi method [Kumazawa et al, 1990] to the source time function of our model crack and found growth rates for our dominant frequency that are consistent with low Q values of 10 -20. Such high attenuation can be attributed to bubbly magma, bubbly water, or steam [e.g., Kumagai and Chouet, 2000;Kumagai et al, 2005].…”
Section: Source Processmentioning
confidence: 99%
“…(64) with observed noise can be reduced to an autoregressive (AR)-type model of the extended Prony method or Sompi method (Kay and Marple, 1981;Kumazawa et al, 1990). These methods are useful in decomposing the transfer function with weak decay, such as in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The coefficients of the AR filter are obtained by solving the modified YuleWalker equation (Marple, 1987) and the coefficients of the MA filter can be estimated using the Durbin method (Kay, 1981;Mars et al, 2004). Alternatively, in the Sompi method, the AR coefficients are obtained by an eigen decomposition of the autocorrelation matrix (Fukao and Suda, 1989;Hori et al, 1989;Kumazawa et al, 1990). The filters obtained from the autocorrelation are minimum phase.…”
Section: Methodsmentioning
confidence: 99%